2013
DOI: 10.1007/s00198-013-2570-8
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of parathyroid hormone on bisphosphonate/steroid-associated compromised osseous wound healing

Abstract: SummaryAdministration of intermittent parathyroid hormone (PTH) promoted healing of tibial osseous defects and tooth extraction wounds and prevented the development of necrotic lesions in rats on a combined bisphosphonate and steroid regimen.IntroductionOsteonecrosis of the jaw (ONJ) has emerged in association with antiresorptive therapies. The pathophysiology of ONJ is unknown and no established cure currently exists. Our objective was to determine the effect of intermittent PTH administration on early osseou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Bashutski et al 33 reported that teriparatide exerted positive effects on healing bone defects in the oral cavity. Teriparatide was reported to be effective in the healing of necrotic wounds in rats administered BPs and steroids by Kuroshima et al 34 In other studies, Kuroshima et al 35 reported that teriparatide promotes healing of the tooth extraction socket. Kuroshima et al 34 in a study associated with BPs and steroids reported that osteoblasts were considerably increased and osteoclasts and necrotic bone were decreased by teriparatide after BP and steroid use.…”
Section: Discussionmentioning
confidence: 97%
“…Bashutski et al 33 reported that teriparatide exerted positive effects on healing bone defects in the oral cavity. Teriparatide was reported to be effective in the healing of necrotic wounds in rats administered BPs and steroids by Kuroshima et al 34 In other studies, Kuroshima et al 35 reported that teriparatide promotes healing of the tooth extraction socket. Kuroshima et al 34 in a study associated with BPs and steroids reported that osteoblasts were considerably increased and osteoclasts and necrotic bone were decreased by teriparatide after BP and steroid use.…”
Section: Discussionmentioning
confidence: 97%
“…Lopez-Jornet et al found that perioperative antibiotics reduced BRONJ incidence after tooth extractions in rats treated with dexamethasone and pamidronate [38]. Three independent studies demonstrated the preventive role of teriparatide, a synthetic recombinant analogue of parathyroid hormone [18,39,40]. Other authors reported the positive effect of the socket mucoperiosteal coverage and of an atraumatic surgical procedure [41,42].…”
Section: Discussionmentioning
confidence: 97%
“…While in general the focus of osteoprotective therapy to date has been antiresorptive treatment, future perspectives portend an improvement of local bone quality (J€ ager et al, 2010;Yamada et al, 2014) as well as an osteoanabolic strategy using a recombinant fragment of the parathyroid hormone teriparatide (Ohbayashi et al, 2013;Kuroshima et al, 2014).…”
Section: Future Perspectivesmentioning
confidence: 97%